Estudio de la producción, beneficiado y comercialización de cacao para la zona de Pucará - Encalada Cuenca, Jessenia Elizabeth (2007)
The present work is part of those "definitive Studies of the Sub one project Intercantonal of benefitted production and commercialization of cocoa in the low areas of Pucará, Ponce Enríquez and Pijilí", proposal that it was developed in Agreement with the M. I. Municipality of Ponce Enríquez, The University of Machala and the Foundation Progress and Development PRODE. The outlined objectives were: 1. Integral diagnosis of the productive and commercial offer. 2. Proposal of improvement continues of the productive system, and of the commercialization system. 3. Integral diagnosis of the structure organizational beneficiary. 4. To outline a structure partner - organizational for viabilizar the installation of the project, with the support of a system of active, equal participation and empoderada with all and each one of the potential partners of the sub-project. The investigation was carried out in the properties cacaoteras of Santa Cecilia's communities, Gramalote, San José, The Palms, Pindo, Chilca Beach and Sarayunga of the Canton Pucará, County of the Azuay. It was carried out in direct form to the primary sources through surveys and personal interviews. The used design was of Descriptive type. The size of the sample was considered it based on the formula that is used in the Subproject Intercantonal. The 63 farmers were chosen at random. As a result of the integral diagnosis of the productive and commercial offer he/she comes off that the drop productivity of the Area is 4,4 qq/ha / year (fresh + dry); the goal to the two years of intervention of the project a production of 6 qq/ha/year, average will be gotten that will be competitive for the producing cocoa. To achieve 35% increase in the production it will be necessary a training process, technical attendance and permanent accompaniment to those producing of cocoa. In a same way 17% of weaknesses exist in the aspect partner - organizational, for that which has been planned the invigoration of the farmer's capacities and the necessity of forming an organizational structure of second grade, with artificial life approved by the organizations involved in the project. The intervention proposal is planned for two years of an intensive training process and technical attendance, it will allow to improve the production levels, to implement the proposal of direct commercialization, eliminating the middlemen that absorb a great margin of utility without carrying out any investment type, for a storing Microcentro will be implemented it located in Sarayunga and it will be administered by the same organization.